Sosialisasi Pencegahan Kekerasan Seksual Pada Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Pattimura - Baharuddin, Wahdaniah; Taufik, Iqbal Johanes; Muammar, Muammar (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The rise of sexual violence has now begun to spread in the higher education environment and almost every university in Indonesia, but the issue of sexual violence is not too exposed in the media, both electronic media and social media, therefore it is necessary to educate about the prevention of sexual violence in the Higher Education environment, because many of them are victims.Purposes of Devotion: Providing education to students about preventing sexual violence in the higher education environment at the Accounting Department, Faculty of Economics and Business, Pattimura University based on Permendikbudristek No. 30 of 2021 concerning Prevention and Handling of Sexual Violence in the Higher Education Environment. Method of Devotion: The method used is to provide legal socialization on the prevention of sexual violence in higher education along with the laws governing sexual violence in higher education. The result of this service activity is to provide students with an understanding of the prevention of sexual violence in higher education.Results of the Devotion: The results of this service are that students gain knowledge and understanding related to the issues of sexual violence that are rampant and efforts to prevent and handle them as a form of creating a campus culture that is safe from sexual violence and makes students feel comfortable to grow into students who excel and have character.